GPX8 regulates pan-apoptosis in gliomas to promote microglial migration and mediate immunotherapy responses - Chen, Zigui; Zheng, Dandan; Lin, Ziren; Zhang, Chunyuan; Wei, Cheng; Deng, Xiandong; Yan, Peng; Zheng, Chuanhua; Lan, Chuanliu; Qin, Chengjian; Wei, Xuanlei; Qin, Deling; et al. (Frontiers in Immunology, 2023)
Introduction Gliomas have emerged as the predominant brain tumor type in recent decades, yet the exploration of non-apoptotic cell death regulated by the pan-optosome complex, known as pan-apoptosis, remains largely unexplored in this context. This study aims to illuminate the molecular properties of pan-apoptosis-related genes in glioma patients, classifying them and developing a signature using machine learning techniques. Methods The prognostic significance, mutation features, immunological characteristics, and pharmaceutical prediction performance of this signature were comprehensively investigated. Furthermore, GPX8, a gene of interest, was extensively examined for its prognostic value, immunological characteristics, medication prediction performance, and immunotherapy prediction potential. Results Experimental techniques such as CCK-8, Transwell, and EdU investigations revealed that GPX8 acts as a tumor accelerator in gliomas. At the single-cell RNA sequencing level, GPX8 appeared to facilitate cell contact between tumor cells and macrophages, potentially enhancing microglial migration. Conclusions The incorporation of pan-apoptosis-related features shows promising potential for clinical applications in predicting tumor progression and advancing immunotherapeutic strategies. However, further in vitro and in vivo investigations are necessary to validate the tumorigenic and immunogenic processes associated with GPX8 in gliomas.